374 Plasma exchange in paediatric nephrology – the irish experience. (11th October 2021) - Wildes, Dermot; Devlin, C; Costigan, CS; Cox, J; Hensey, C; Waldron, M; Dolan, N; Riordan, M; Sweeney, C; Stack, M; Raftery, T; Cotter, M; et al.
Abstract : Plasma exchange (PLEX) has proven an effective modality in the management of many paediatric renal conditions. Despite its widespread acceptance, and advancements in the practice of apheresis, there remains a paucity of data pertaining to the paediatric patient population. The use of PLEX in paediatric patient cohorts is technically more challenging than in their adult counterparts, due to numerous factors which include the patient's size, extracorporeal circulatory volume, ability to tolerate therapy and the difficulties regarding care of vascular-access ports in a younger cohort. 1 Given the lack of data surrounding PLEX in Paediatrics, protocols are developed based on extrapolations from best-practice in adult populations, an area where work must be carried out to improve patient safety and outcome. We present a large cohort of paediatric patients undergoing therapeutic plasma exchange therapy for solely renal indications, across a period of 17 years. A retrospective chart review was conducted for all patients (under 16 years) undergoing PLEX therapy for a renal indication, as specified by the ASFA Guidelines, between January 2002 &amp June 2019. 2 The following data were extracted, for each individual case: Age; gender; indication; complications; pre-medications; therapeutic outcome. Patients were stratified into groups as follows: STEC HUS; aHUS; Nephritis (C3GN, PIGN, anti-GBM, ANCA Vasculitis); IgA Nephropathy/HSP; Post-Transplant (recurrent FSGS, acute humeral rejection). This review was performed with permission from the CHI at Temple Street Research & Ethics Committee. A total of n=58 patients were identified, 39.7% were male (n=23) and 60.3% were female (n=35). 1137 exchanges were performed. The median age of patients undergoing PLEX was 35.5 months. The most common indication was STEC HUS (n=29). Fluid substitution was performed using 5% Albumin-Saline or Plasma. Complications occurred in n=38 patients, with most experiencing minor complications. Asymptomatic hypocalcaemia was the most common complication experienced (n=25). There were no deaths as a result of PLEX therapy. We present our experience of plasma exchange (PLEX) therapy, spanning 1, 137 exchanges across 17 years, proved a well-tolerated, highly efficacious therapy for a variety of renal pathologies, as listed above. Most complications experienced were minor in nature, and with therapy conducted in specialised centres, with appropriately paediatric-trained staff, there are very low levels of adverse events – most of which can be anticipated. References: Goldstein SL. Therapeutic apheresis in children: special considerations. Semin Dial 2012 Mar-Apr;25(2):165-70. doi:10.1111/j.1525-139X.2011.01028.x. Epub 2012 Jan 25. PMID: 22277133. Connelly-Smith L, Dunbar NM. The 2019 guidelines from the American Society for Apheresis: what's new?. Curr Opin Hematol 2019;26(6):461-465. doi:10.1097/MOH.0000000000000534